Fabrication and characterization of a nanostructured TiO2/In2S3-Sb2S3/CuSCN extremely thin absorber (eta) solar cell - Huerta Flores, Alí Margot; García Gómez, Nora Aleyda; Parra Arciniega, Salomé Maribel de la; Sánchez Cervantes, Eduardo Maximiano (Institute of Physics, 2016)
CuSCN extremely thin absorber solar cell. Nanostructured TiO2 deposited by screen printing on an ITO substrate was used as an n-type electrode. An ∼80 nm extremely thin layer of the system In2S3-Sb2S3 deposited by successive ionic layer adsorption and a reaction (silar) method was used as an absorber. The voids were filled with p-type CuSCN and the entire assembly was completed with a gold contact. The solar cell fabricated with this heterostructure showed an energy conversion efficiency of 4.9%, which is a promising result in the development of low cost and simple fabrication of solar cells.